2018
DOI: 10.1016/j.celrep.2018.10.094
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Accumulation of Ribosome-Associated Isolated 3′ UTRs in Neuronal Cell Populations of the Aging Brain

Abstract: SUMMARY Particular brain regions and cell populations exhibit increased susceptibility to aging-related stresses. Here, we describe the age-specific and brain-region-specific accumulation of ribosome-associated 3′ UTR RNAs that lack the 5′ UTR and open reading frame. Our study reveals that this phenomenon impacts hundreds of genes in aged D1 spiny projection neurons of the mouse striatum and also occurs in the aging human brain. Isolated 3′ UTR accumulation is tightly correlated with mitochondrial gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 49 publications
(83 reference statements)
9
57
0
Order By: Relevance
“…Finally, we noted an interesting accumulation of the 3'UTR region of histone gene HIST2H2BE in both senescent and EXOSC3-depleted cells ( Figure 1K). This phenomenon was reminiscent of the accumulation of 3'UTRs previously described in the aging mouse brain (11).…”
Section: Reduced Rna Turnover In Senescent Cellssupporting
confidence: 59%
See 1 more Smart Citation
“…Finally, we noted an interesting accumulation of the 3'UTR region of histone gene HIST2H2BE in both senescent and EXOSC3-depleted cells ( Figure 1K). This phenomenon was reminiscent of the accumulation of 3'UTRs previously described in the aging mouse brain (11).…”
Section: Reduced Rna Turnover In Senescent Cellssupporting
confidence: 59%
“…Some observations are suggestive of a more comprehensive impact of RNAs in cellular senescence, via their production, their maturation, or their turn-over. For example, it was reported that in the aging mouse brain, some neurons start accumulating 3′ untranslated regions (UTRs), resulting in the production of small peptides of yet unknown function (11). In parallel, transcripts from SINEs/Alus, a family of repetitive elements particularly abundant in euchromatin, have been reported to accumulate in senescent cells with an impact on genome integrity (12).…”
Section: Introductionmentioning
confidence: 99%
“…Proteasome activity is further reduced in the old brain, correlating with an increased imbalance between the 19S and 20S complexes with time ( Figure 5B and 5C). In addition, altered stoichiometry of the ribosome can underlie both the reduction and the qualitative changes of protein synthesis in brain aging (Ori et al, 2015;Schimanski and 5 Barnes, 2010; Sudmant et al, 2018). An alteration of the stoichiometry between membranebound and cytosolic components of the lysosomal v-type ATPase ( Figure 2F) might influence the acidification of lysosomes and the activation of mTORC1 (Zoncu et al, 2011), thus hampering the clearance of protein aggregates.…”
mentioning
confidence: 99%
“…However, this overall slight reduction in protein synthesis is unlikely to account for the selective inhibition of NMD on a fraction of the NMD targets, and moreover the puromycylation assay does not address which step of translation is affected by ABCE1 KD. There is evidence that ABCE1 depletion causes ribosome stalling at termination codon and an increased ribosome occupancy in the 3'UTR, suggesting mainly an impairment of translation termination (Mills et al, 2016;Sudmant et al, 2018;Young et al, 2015). According to this model, mRNAs are expected to still be associated with polysomes upon ABCE1 KD, and strong association of mRNAs with polysomes would provide indirect evidence that these mRNAs are still actively translated.…”
Section: Nmd Sensitive Mrnas Are Strongly Associated With Polysomes Imentioning
confidence: 99%